LsARF3 mediates thermally induced bolting through promoting the expression of LsCO in lettuce (Lactuca sativa L.) - Li, Yunfeng; Zhu, Jiaqi; Feng, Yixuan; Li, Zhenfeng; Ren, Zheng; Liu, Ning; Liu, Chaojie; Hao, Jinghong; Han, Yingyan (Frontiers in Plant Science, 2022)
Lettuce (Lactuca sativa L.) is a leafy vegetable whose edible organs usually are leaf or stems, and thus high-temperature induced bolting followed by flower initiation is an undesirable trait in lettuce production. However, the molecular mechanism that controls lettuce bolting and flowering upon thermal treatments is largely unknown. Here, we identified a Lettuce auxin response factor 3 (LsARF3), the expression of which was enhanced by heat and auxin treatments. Interestingly, LsARF3 is preferentially expressed in stem apex, suggesting it might be associated with lettuce bolting. Transgenic lettuce overexpressing LsARF3 displayed early bolting and flowering, whereas knockout of LsARF3 dramatically delayed bolting and flowering in lettuce under normal or high temperature conditions. Furthermore, Exogenous application of IAA failed to rescue the late-bolting and -flowering phenotype of lsarf3 mutants. Several floral integrator genes including LsCO, LsFT, and LsLFY were co-expressed with LsARF3 in the overexpression and knockout lettuce plants. Yeast one-hybrid (Y1H) experiments suggested that LsARF3 could physically interact with the LsCO promoter, which was further confirmed by a dual luciferase assay in tobacco leaves. The results indicated that LsARF3 might directly modulate the expression of LsCO in lettuce. Therefore, these results demonstrate that LsARF3 could promote lettuce bolting in response to the high temperature by directly or indirectly activating the expression of floral genes such as LsCO, which provides new insights into lettuce bolting in the context of ARFs signaling and heat response.